Fuel System Types for Modern Vehicles (Eurasian Journal of Engineering and Technology, 2023)
One of the most urgent issues is to reduce the amount of toxic gases released into the environment and transition to an alternative fuel supply system. The following countries are conducting scientific research on modern carburetors and injectors.